Ab initio complex potential energy curves of the He*(1s2p 1P)-Li dimer - Landau, Arik; Ben-Asher, Anael; Gokhberg, Kirill; Cederbaum, Lorenz S.; Moiseyev, Nimrod (The journal of chemical physics, 2020)
LiHe is an intriguing open-shell dimer. It is an extremely weakly bound system, and its vibrational bound-state radius extends far into the classically forbidden regions. Exciting helium into 1s2p leads to a 2Σ and a 2Π state, in which lithium is in its ground state. These states are located above the ionization threshold of the Li atom, which makes them metastable, i.e., resonance states. Under these conditions, energy transfer between the atoms over large distances is feasible within the framework of interatomic Coulombic decay (ICD). These states are investigated theoretically; herein, we present and analyze the complex potential energy curves of the 2Σ and 2Π states, where their imaginary parts describe the decay rate of these resonance states. We resonance via Padé approach to calculate these potentials. Thereby, we use the equation-of-motion coupled-cluster method to compute stabilization graphs as input data for the analytical dilation (via Padé) into the complex energy plane. The procedure is suitable for studying Feshbach resonances and ICD states such as the LiHe 2Σ and 2Π states. The resulting ab initio complex potential energy curves will be used in future work to describe the dynamics of the process HeLi + hν → He*Li → HeLi+ + eICD, which is amenable to experiment.
Im Titel ist die Zahl 1 vor P hochgestellt
Gesehen am 04.06.2020